2013
DOI: 10.1590/s0102-86502013000200009
|View full text |Cite
|
Sign up to set email alerts
|

The use of mitomycin C in caustic esophagitis in rats

Abstract: PURPOSE:To evaluate the topical effects of mitomycin C (MMC) in rats, with or without esophageal dilation, in different moments after esophageal caustic injury with NaOH10%. METHODS:Forty eight Wistar rats were divided into six groups: "GS" infusion of 0.9% saline solution in the esophagus; "CG" infusion of 0.9% saline solution in the esophagus, with temporary ligation of the organ; "NTG" induction of a caustic lesion without treatment; "GmmcD0" MMC applied immediately after the caustic injury; "GmmcD14" MMC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The local experience in Denmark, Israel, United Kingdom, Peru, Spain, Australia, Saudi Arabia and Turkey has shown that alkaline agents mostly cause caustic injury 9 . NaOH, known as the sink openers, is the most well-known and most used in experimental studies among alkaline agents 10 . Therefore, in our study, we created the esophagitis model using NaOH.…”
Section: Discussionmentioning
confidence: 99%
“…The local experience in Denmark, Israel, United Kingdom, Peru, Spain, Australia, Saudi Arabia and Turkey has shown that alkaline agents mostly cause caustic injury 9 . NaOH, known as the sink openers, is the most well-known and most used in experimental studies among alkaline agents 10 . Therefore, in our study, we created the esophagitis model using NaOH.…”
Section: Discussionmentioning
confidence: 99%